Piano Sonata no. 7 in D major, op. 10, no. 3, edited by Knorr - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Knorr, Julius, 1807-1861 (editor):::Contributor:::::::::::: (Germany; J. André; Offenbach am Main, 2024)
Piano Sonata no. 7 in D major, op. 10, no. 3, edited by Julius Knorr and published in volume 1 of the collection "Sonaten, Variationen etc. für Pianoforte allein componirt von L. van Beethoven" by J. André in Offenbach am Main and Augener & Co. in London.